What’s Law Got To Do With It? The Role of the Law in Creating and Exacerbating Racial Disparities in Colonial Land Grants after the War of 1812 - Marsman, Melisa (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2025)
While the reciprocal relationship between law and race is complex and multifaceted, it has deep historical roots in colonial legal systems that played a crucial role in producing and perpetuating racial inequalities. The effects of these historical injustices persist today, evident in the numerous examples of racial disparities across various aspects of life, including land ownership. This article aims to uncover the role of settler-colonial land laws in creating and exacerbating land-based racial inequalities in colonial land grants, with a specific focus on those affecting the Black Refugees of the War of 1812.